Phillygenin Protects the Intestinal Barrier from Dysfunction via let-7b Signaling Pathway and Regulation of Intestinal Microbiota. (16th March 2022) - Feng, Huiping; He, Ling; Wang, Zihua; Pi, Bin; Liu, Zhihua
Abstract : The study investigates the positive effects of phillygenin on intestinal tight junction via the let-7b signaling pathway and the regulation of intestinal microbiota. The expression levels of tight junction proteins are determined through PCR and Western blot. DSS-induced mice colitis is used to verify the protective effects of phillygenin on intestinal barrier and tight junction. Fecal microbiota transplantation is used to verify the role intestinal microbiota. let-7b is detected in the colon tissues of patients with acute stercoral obstruction. Phillygenin could promote the expression of occludin, which might be inhibited by let-7b inhibitor. DSS-induced mice colitis showed that phillygenin could lower the colonic permeability and maintain the tight junction-associated proteins. The effects of phillygenin could be deprived by anti-let-7b and rescued by FMT of normal intestinal microbiota. Clinical samples verified a lower level of let-7b in stercoral obstruction patients. Phillygenin could protect the intestinal barrier from dysfunction via the signaling pathway of let-7b by regulating intestinal microbiota.